2023
DOI: 10.3389/fmars.2023.1066050
|View full text |Cite
|
Sign up to set email alerts
|

Computing marine plankton connectivity under thermal constraints

Abstract: Ocean currents are a key driver of plankton dispersal across the oceanic basins. However, species specific temperature constraints may limit the plankton dispersal. We propose a methodology to estimate the connectivity pathways and timescales for planktonspecies with given constraints on temperature tolerances, by combining Lagrangian modeling with network theory. We demonstrate application of two types of temperature constraints: thermal niche and adaptation potential and compare it to thesurface water connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…These findings are in line with those obtained by Siokou et al (2019) in the Mediterranean Sea, who observed differentiation between Eastern and Western Mediterranean mesozooplankton communities at lower mesopelagic and bathypelagic depths, but no differentiation at epipelagic and upper mesopelagic layers. These results point to lower connectivity between deep-sea mesozooplankton communities than between communities from upper oceanic layers, which may be driven by limitations in the dispersal of mesozooplankton assemblages at the ocean depths due to prevailing weaker oceanic currents and water mixing in the deep sea compared to the surface (Manral et al, 2023;Reid, 1981Reid, , 1994-in agreement with previous findings for picoeukaryotes (Villarino et al, 2022). Our findings add further evidence on the major role of oceanic currents in shaping zooplankton dispersal and connectivity at a global scale, not only at epipelagic layers as previously reported (Richter et al, 2020;Villarino et al, 2018;Watson et al, 2011), but, for the first time for mesozooplankton, also at the ocean depths.…”
Section: The Deeper the Lower The Connectivity Between Mesozooplankto...supporting
confidence: 91%
See 1 more Smart Citation
“…These findings are in line with those obtained by Siokou et al (2019) in the Mediterranean Sea, who observed differentiation between Eastern and Western Mediterranean mesozooplankton communities at lower mesopelagic and bathypelagic depths, but no differentiation at epipelagic and upper mesopelagic layers. These results point to lower connectivity between deep-sea mesozooplankton communities than between communities from upper oceanic layers, which may be driven by limitations in the dispersal of mesozooplankton assemblages at the ocean depths due to prevailing weaker oceanic currents and water mixing in the deep sea compared to the surface (Manral et al, 2023;Reid, 1981Reid, , 1994-in agreement with previous findings for picoeukaryotes (Villarino et al, 2022). Our findings add further evidence on the major role of oceanic currents in shaping zooplankton dispersal and connectivity at a global scale, not only at epipelagic layers as previously reported (Richter et al, 2020;Villarino et al, 2018;Watson et al, 2011), but, for the first time for mesozooplankton, also at the ocean depths.…”
Section: The Deeper the Lower The Connectivity Between Mesozooplankto...supporting
confidence: 91%
“…We hypothesise: i) that unexplored oceanic regions, such as the deep sea, harbour a higher proportion of hidden mesozooplankton diversity than those from upper layers, ii) that mesozooplankton communities are subjected to vertical and horizontal oceanic gradients at a global scale, which generate global biogeographic patterns, and iii) that mesozooplankton spatial distribution and connectivity differ at the different ocean layers, with higher dissimilarity between deep-sea communities than between communities at upper layers due to the average weaker deep-sea currents compared to surface ones (Manral et al, 2023;Reid, 1994).…”
Section: Studies Analysing the Global Distribution And Connectivity O...mentioning
confidence: 99%
“…Fully pelagic species such as planktonic organisms generally have high dispersal potential between very distant locations (e.g. the entire Atlantic Ocean) given enough time although environmental constraints such as temperature or salinity may impose limitations in connectivity (Manral et al 2023). Zoogeographical evidence suggests that the dispersal of many pelagic species is more likely to be limited by their ability to maintain viable populations rather than hydrographic barriers (Noris 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Zooplankton organisms have limited motility for long distances and depend on ocean currents to move horizontally. Advection of plankton by ocean currents is the primary factor driving the ecosystem dynamics in the upper pelagic zone (Manral et al., 2023). Oceanographic processes that affect plankton transport and distribution act in a continuum of spatial scales.…”
Section: Introductionmentioning
confidence: 99%